Implementation of Cloth Simulation Using Parallel Computing on Mobile Device - JaeHong Jeon; Se Dong Min; Min Hong (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Physically based modeling and simulation is an important technique for deformable object simulation, which is widely used to represent the realistic shape change and movement of objects for mobile game or 3D simulation. However, they require the high computational cost for representing the physical phenomenon on deformable objects when it applied on mobile device. In this paper, we designed and implemented the cloth simulation for deformable object simulation using the parallel technique on mobile device to optimize the computational burden. We especially applied GPU parallel technique for the integration solving process such as Euler, Midpoint, 4th-order Runge-Kutta method to estimate the particles' next status using positions and velocities. Also we applied multi-thread parallel technique for calculating the spring force. Then we compared the performance of each integration methods between under only CPU and CPU with GPU on mobile device. Also we compared the computing time of spring calculation between only CPU and using CPU multi-thread.